Interfaith Dialogue - Ariarajah, S. Wesley (The ecumenical review, 2019)
The modern ecumenical movement initially sprang from the missionary movement. This led to considerable struggle within the ecumenical movement over embracing interfaith dialogue as a main focus of its ministry. This focus was eventually accepted, and since then the ecumenical movement has done much to promote interfaith relations at the local, national, and global level; to struggle with the theological issues such dialogue presents for the Christian faith; and to collaborate with other religions to reflect on common issues faced by the global community. Current Dialogue has played a major role in promoting the dialogue concern.